Inventory of species and analysis of stomata characteristics of shade trees at UIN Walisongo Semarang - Khasanah, Rita Ariyana Nur; Na’ima , Mirtaati (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
The presence of shade trees has ecological function to reduce air pollution level. The part of leaves, stomata is responsible for the function. The study aimed to inventory species and analyze the characteristics of leaf stomata of shade trees at UIN Walisongo Semarang. This exploratory research was conducted in September-October 2021. Observation method throughout the campus area was carried out by using observation sheet. Some representative books and articles were used as references. For stomata observation, leaf samples were taken by purposive sampling. Paradermal preparations were made by wholemount method. All data were analyzed descriptively. The results showed that there were about 17 families, 37 species and 712 individual species of shade trees growing on campus 2-3. Then, there were about 8 families, 8 species and 138 individual species of shade trees growing on campus 1. The highest number of trees in both location was Glodogan Tiang. There were about 7 families, 7 species, and 194 individual species of shade trees recently planted on campus 2-3. Stomata characteristics (type, distribution, length and width, pore length and width, number, and density) differed in each species. The largest stomata size and pore were found in in abaxial leaves of Nyamplung whereas the highest stomata density was found in abaxial leaves of Mahagony. Pore size and density of stomata were related to the ability of leaves to reduce air pollution level. The shade tree data obtained in this study showed plant diversity in the campus.